2010
DOI: 10.5539/ijb.v2n1p143
|View full text |Cite
|
Sign up to set email alerts
|

Gas Exchange, Chlorophyll and Growth Responses of Betula Platyphylla Seedlings to Elevated CO2 and Nitrogen

Abstract: Effects of elevated [CO 2 ] and nitrogen nutrition on leaf gas exchange, chlorophyll content and growth in Betula platyphylla seedlings were studied. The seedlings were grown in the ambient [CO 2 ] (AC, 350 mol mol -1 ) and elevated [CO 2 ] (EC, 700 mol mol -1 ) growth chambers, with three levels of nitrogen: LN (0mmol L -1 N), MN (1.5mmol L -1 N) and HN (3mmol L -1 N). HN increased photosynthesis (P max ), photochemical efficiency of PSII (F v /F m ) and intercellular [CO 2 ] (C i ) by 120%, 8% and 11% than … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 15 publications
2
10
2
Order By: Relevance
“…High soil nitrogen supply enhanced the absorption rate of leaves due to increased chlorophyll content (Singh and Agrawal, 2015). A similar finding had been reported by Zhao et al (2010). PGPR can have an important role in increasing the amount of nitrogen through fixation of atmospheric nitrogen.…”
Section: Effect Of Treatments On Leaf and Petal Pigmentssupporting
confidence: 81%
“…High soil nitrogen supply enhanced the absorption rate of leaves due to increased chlorophyll content (Singh and Agrawal, 2015). A similar finding had been reported by Zhao et al (2010). PGPR can have an important role in increasing the amount of nitrogen through fixation of atmospheric nitrogen.…”
Section: Effect Of Treatments On Leaf and Petal Pigmentssupporting
confidence: 81%
“…It was reported that CO 2 supplementation limits the uptake of N and the synthesis of nitrogenous compounds of vegetables by 9.5% [47]. In the literature, it was reported among different mineral elements that Fe concentration experienced the greatest decrease (31%) in leafy greens grown under supplemented CO 2 conditions [17]. In the current study, contrasting results were seen for basil 'Cardinal' where Fe concentration increased significantly in CO 2 supplemented conditions.…”
Section: Discussioncontrasting
confidence: 66%
“…Similar to the present study, Gillig et al [32] also reported a significant decrease in chlorophyll level in hydroponically grown basil when grown at 400 and 1500 ppm CO 2 . Similarly, development of interveinal chlorosis was observed due to the accumulation of large grains of starch in basil grown under 1500 ppm CO 2 concentration [17]. The chlorophyll level under supplemented CO 2 can be explained by movement of N to other sinks or it may be due to degradation of the chlorophyll [37].…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…In addition, a small decrease in Rubisco content via suppression of Rubisco small subunit (RBC) genes led to increased chlorophyll content under eCO 2 conditions [16]. In contrast, the chlorophyll content was significantly reduced under eCO 2 conditions in some seedling experiments [66,67].…”
Section: Pnue and N Allocation Under Eco2 Conditions And N Fertilizationmentioning
confidence: 99%